2015
DOI: 10.1681/asn.2014050528
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-Interacting Protein Deficiency Protects against Diabetic Nephropathy

Abstract: Expression of thioredoxin-interacting protein (TxNIP), an endogenous inhibitor of the thiol oxidoreductase thioredoxin, is augmented by high glucose (HG) and promotes oxidative stress. We previously reported that TxNIP-deficient mesangial cells showed protection from HG-induced reactive oxygen species, mitogenactivated protein kinase phosphorylation, and collagen expression. Here, we investigated the potential role of TxNIP in the pathogenesis of diabetic nephropathy (DN) in vivo. Wild-type (WT) control, TxNIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 51 publications
(90 reference statements)
6
73
0
Order By: Relevance
“…Importantly, our experiments with THP1 cells cultured under various HG/NG conditions revealed an association between persistent DNA-me triggered by prior history of HG exposure and enhanced TXNIP expression in response to HG in vitro. We, thus, speculate that transient hyperglycemic episodes during the EDIC Study would induce more TXNIP overexpression and cellular dysfunction in cases vs. controls because of TXNIP hypo-me, which is in line with the reported adverse cellular roles of TXNIP (43)(44)(45)48). This type of cellular response to episodic HG provides mechanistic information toward understanding the connections between persistent DNA hypo-me at TXNIP and its gene expression and hence, metabolic memory of diabetic complications.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Importantly, our experiments with THP1 cells cultured under various HG/NG conditions revealed an association between persistent DNA-me triggered by prior history of HG exposure and enhanced TXNIP expression in response to HG in vitro. We, thus, speculate that transient hyperglycemic episodes during the EDIC Study would induce more TXNIP overexpression and cellular dysfunction in cases vs. controls because of TXNIP hypo-me, which is in line with the reported adverse cellular roles of TXNIP (43)(44)(45)48). This type of cellular response to episodic HG provides mechanistic information toward understanding the connections between persistent DNA hypo-me at TXNIP and its gene expression and hence, metabolic memory of diabetic complications.…”
Section: Discussionsupporting
confidence: 66%
“…Persistence of DNA hypo-me in TXNIP at two time periods was particularly interesting, because TXNIP is a reported sensor of glucose stress, a prooxidant, and a proapoptotic protein, with gene expression that is highly associated with hyperglycemia and diabetic complications, including retinopathy and nephropathy (43)(44)(45), both of which were prevalent in our case group. TXNIP expression is highly induced by HG in various cell types (46)(47)(48), which by inhibiting thioredoxin, subsequently causes oxidative stress and apoptosis.…”
Section: Resultsmentioning
confidence: 90%
“…Here we did not perform immunostaining for pAMPK localization in the rat kidney. Other researchers have demonstrated, by immunohistochemistry, increased TGF-β expression in both tubular and glomerular compartments in rodent models after 8, 12 and 24 weeks of diabetes555657. Since TGF-β is downstream to the other components of the fibrogenic pathway we studied, it is likely that the changes we observed are also present in glomerular and tubular compartments.…”
Section: Discussionsupporting
confidence: 50%
“…Although both molecular 28 and topological 5 observations indicate that the role of TxnIP in promoting oxidative injury extends beyond its negative regulation of Trx, augmented expression of the protein has been repeatedly associated with the development of diabetes complications. 5,[29][30][31][32] In this study, we found that depletion of EZH2, with either DZNep or shRNA, rendered cultured podocytes vulnerable to the deleterious effects of high-glucose concentrations, leading to an increase in ROS levels and cell death. The augmentation of high glucose-induced oxidative damage in podocytes was, at least in part, mediated by derepression of TxnIP shown by (1) increased podocyte TxnIP mRNA and protein abundance when EZH2-depleted cells were exposed to high-glucose concentrations and (2) abrogation of ROS accumulation by either TxnIP knockdown or Trx overexpression.…”
Section: Discussionmentioning
confidence: 68%